Pengaruh Kompetensi Manajerial Kepala Madrasah Terhadap Kinerja Guru Pada Madrasah Aliyah di Makassar - Musafir Thahir (Universitas Muslim Indonesia, 2022)
The purpose of this study was to determine and analyze the effect of managerial competence of the Head of Public and Private Madrasah on teacher performance at madrasah Aliyah in Makassar. This research was conducted at Public and Private Aliyah Madrasahs in Makassar City with a population of 530 teachers from 25 Madrasah Aliyah (Public and Private). The sample determination used the slovin formula, namely 20 Madrasah Aliyah and 84 respondents. The data analysis used is descriptive analysis to explain research data and research descriptions, while to analyze quantitative data using multiple linear regression analysis tools. The results of this study prove that simultaneously the hypothesis of H0 diterma and H1 is rejected, namely the managerial competence of the Head of Public and Private Aliyah Madrasah simultaneously has no positive and significant effect on the performance of Madrasah Aliyah teachers in Makassar.And vartially, H0 hypetesis was accepted and H1 was rejected, namely the managerial competence of the Head of the Public and Private Aliyah Madrasah both did not have a positive and significant effect on the performance of madrasah Aliyah teachers in Makassar